Single-beam three-axis optically pumped magnetometers with sub-100 femtotesla sensitivity. (26th May 2021) - Xiao, Wei; Wu, Yulong; Zhang, Xiangzhi; Feng, Yulong; Sun, Chenxi; Wu, Teng; Chen, Jingbiao; Peng, Xiang; Guo, Hong
Abstract: We demonstrate a single-beam three-axis parametric-resonance magnetometer operated in near-zero fields. By reflecting the incident laser beam at 90° in the vapor cell and applying three orthogonal parametric modulation fields, the three components of the magnetic field can be extracted from the transmitted light signal. Our vector magnetometer experimentally demonstrates magnetic-field sensitivities of 30 fT Hz −1/2 along x - and y -axes and 70 fT Hz −1/2 along the z -axis, and features a compact single-beam architecture, which is particularly attractive for applications requiring highly sensitive measurements of the vector components of magnetic fields with low power consumption and miniaturized magnetometers, such as magnetoencephalography and magnetocardiography.